Tetramethylpyrazine Induces Apoptosis and Inhibits Proliferation of Hypertrophic Scar-Derived Fibroblasts via Inhibiting the Phosphorylation of AKT - Wu, Xue; Wang, Zheng; Wu, Gaofeng; Xu, Xiaofan; Zhang, Jian; Li, Yan; Zhang, Hong; Guo, Shuzhen (Frontiers in Pharmacology, 2020)
Hypertrophic scar (HS) is a serious fibrotic skin disease and often considered as a kind of benign skin tumor. Tetramethylpyrazine (TMP), the main chemical composition of the traditional Chinese medicine Chuanxiong Rhizoma, has shown significant clinical benefits in the treatment of fibrosis disease and tumor, while the role in HS and the concrete mechanisms remain elusive. Herein, the protective effects of TMP in the treatment of HS was investigated and the results showed that the protein expression levels of type I collagen (Col I), type III collagen (Col III) and α-smooth muscle actin (α-SMA) were all inhibited remarkably after addition of TMP in HS-derived fibroblasts (HFs). Moreover, TMP also suppressed fibroblast proliferative and induced cell apoptosis. The protein expression levels of Caspase-3 and Bcl-2 were all decreased comparing with the control group while proapoptotic proteins Bax and Cleaved Caspase-3 were increased. In addition, TMP treatment markedly reduced the phosphorylation levels of AKT. Taken together, our investigations demonstrated that TMP could down-regulate the expression of fibrosis-related molecules, inhibit scar fibroblast proliferation and activate cell apoptosis, during which AKT pathway was involved. Thus, this study shed more light on the pharmacological mechanisms of TMP, and provided a novel therapeutic alternative for prevention and treatment of HS.